Tradition and Development of Lithuanian Terminology - Antanas Smetona (Lietuvių Kalba)
The development of Lithuanian terminology has undergone several stages. The first stage is characterised by elemental terminology development, marked by unsystematic progress before the Industrial Revolution. Due to Lithuania’s socio-cultural circumstances—such as the prevalence of science in international languages, the absence of a standardised public Lithuanian language, occupation, and its peripheral status within the empire—terminology primarily relied on the spoken folk language, lacking a structured scientific foundation. The second stage aligns with Lithuania’s industrial revolution in the middle of the 19th century. With advancements in industry, science, education, the press, and the popular scientific literature, there emerged a demand for new, systematic Lithuanian terminology. The resources from previous centuries proved insufficient in both quality and quantity. Consequently, alongside original Lithuanian terminology, a considerable number of translated terms, calques, and foreign language influences emerged, leading to synonymy issues. Often a patriot or a man of science, who has returned or is returning to the Lithuanian language, has, to put it mildly, insufficient knowledge of Lithuanian word formation and grammar, and hence the rather poor quality of terminology emerges. The third stage of development marks the beginning of systematic and conscious work on terminology, the recognition of terminology as an important auxiliary scientific discipline, and the postulation of its principles in the first half of the 20th century. It is during this period that textbooks and systematic dictionaries were produced in various fields of science (mathematics, geometry, zoology, engineering, philosophy, law, etc.). Even administrative resources are used, with the creation of terminology commissions in various subject areas. It is at this moment that the terminology genius of Stasys Šalkauskis stands out because by creating and reflecting on the terminology of philosophy, he lays the foundations of the science of Lithuanian terminology. His ideas are in line with those of Eugen Wüster, who is considered to be the founder of terminology. The fourth stage of terminology development coincides with the Soviet occupation. Despite the complex situation and language dynamics, the publication of term dictionaries in diverse scientific fields flourished. Notably, all education, from primary school to dissertation defence, was available in the Lithuanian language. Although the influence of Russian was strong and the Soviet school dominated terminology science, this period witnessed substantial development. The fifth stage refers to the recent post-independence times. Terminology work has become much more lively and varied, acquiring a truly international character, and Western ideas of terminology have been widely adopted. A national language policy has emerged. Unfortunately, against the background of the general equality of the languages of the European Union, the language of science is increasingly becoming English, and the number of scientific publications in Lithuanian is decreasing. Therefore, it is sometimes worrying to think what lies ahead for the science of terminology in Lithuania and for the Lithuanian terminology. The science of terminology is young. Both in Europe and in Lithuania. It may have its roots in the early 19th century, but the time of its formation is the middle of the 20th century. However, during this short period of time, due to the efforts of terminologists—both linguists and specialists in the subject areas - the Lithuanian terminology has successfully played its proper role in the Lithuanian language of science and technology. The hope is that the morbidly perceived internationality will not overshadow the Lithuanian language altogether and that the new winds of life will not hinder the development of Lithuanian terminology, which will continue to serve the intellectual life of the Lithuanian nation, despite “occasional setbacks”.